69PIrinotecan and cisplatin therapy-induced neutropenia as a prognostic factor in patients with extensive-disease small cell lung cancer. (24th November 2019) - Ishikawa, H; Tsuji, D; Miyagi, T; Kawasaki, Y; Yamamoto, K; Nakao, M; Nakagaki, S; Hayashi, T; Ayuhara, H; Harada, T; Tamaki, S; Maeda, A; et al.
Abstract: Background: Chemotherapy-induced neutropenia (CIN) is a dose-limiting toxicity of many chemotherapy agents. Recently, CIN has been associated with longer survival time in various types of cancer, suggesting a role as a prognostic factor. However, no large-scale study has yet investigated the utility of CIN as a prognostic factor in small cell lung cancer. We therefore conducted this multicenter retrospective observational study to investigate the utility of CIN as a prognostic factor for overall survival (OS) in patients with extensive-disease small-cell lung cancer (ED-SCLC) treated with chemotherapy. Methods: Clinical data, including data on CIN onset during chemotherapy, were collected from electronic medical records of patients with ED-SCLC who received standard-dose irinotecan and cisplatin (IP regimen) as primary therapy at 14 participating institutions across Japan between January 1, 2012 and December 31, 2016. Landmark analysis, with the association between OS and neutropenia as the primary endpoint was performed with 102 patients who completed all four cycles of the IP regimen and whose OS was ≥112 days. Univariate analysis using the log-rank test and multivariate analysis using the Cox proportional hazards model with factors previously identified as possible prognostic factors as covariates were also performed to examine the association between CIN and OS. Results: Analysis of median OS by grade among patients who developed CIN revealed significantly longer survival in the group with grade 4 CIN (633 days, 95% confidence interval [CI]: 379–757) than in the group with grade 0 to 3 CIN (444 days, 95% CI: 360–505) (P = 0.0279). Multivariate analysis suggested that lactate dehydrogenase (LDH) of ≥ 230 IU/L (hazard ratio [HR]: 2.937; 95% CI: 1.739–4.958, P < 0.001) and grade 0 to 3 CIN (HR: 2.096; 95% CI: 1.151–3.818, P = 0.0156) are independent poor prognostic factors for ED-SCLC. Conclusions: Onset of grade 4 CIN was associated with longer OS in patients with ED-SCLC. Our results also show that both LDH and CIN may be prognostic factors in patients treated using the IP regimen. Clinical trial identification: This study was approved by the Institutional Review Board of our institution (approval no: T29-8-30-2-3). Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.